Growth and Development of Children Suffering From HIV/AIDS - Ernawati Ernawati (Universitas Muhammadiyah Semarang, 2018)
HIV infection increases the need for energy and nutrients. The presence of opportunistic infections in HIV / Aids will produce neurological symptoms and impact on growth and development of children. The general purpose of this research is to know a picture of the growth and development of children infected with HIV / Aids.Qualitative research methods with the case study method. Participants were 6 children with HIV-positive status in the age range 0-6 years were selected purposively carried out in the district of Kudus.The study found growth and development of children with HIV-positive status where CD4 still at a normal level, tends to normal. They seemed to move like other normal children. While children with low CD4 conditions will be susceptible to opportunistic infections and often sickly. Symptoms in the mouth such as mouth ulcers, oropharyngeal thrush and candida esophagitis can lead to decreased food intake. In addition gastrointestinal disorders and food intolerance can cause diarrhea is more common in children with HIV/ Aids. This will have an impact on growth is weight loss and nutritional status. Further nursing interventions necessary to minimize the appearance of opportunistic diseases and symptoms of early stimulation development of children with HIV /Aids.